2022
DOI: 10.3390/nu14194069
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of a Pea–Clam Two-Peptide Composite on Hypertension and Organ Protection in Spontaneously Hypertensive Rats

Abstract: In the present study, we prepared pea peptides with high angiotensin-converting enzyme (ACE) inhibitory activity in vitro using an enzymatic hydrolysis of pea protein and compounded them with clam peptides to obtain a pea-clam double peptide. The effects of the two-peptide composite and pea peptides on hypertension and the damage-repair of corresponding organs were studied in spontaneously hypertensive rats (SHRs). We found that both pea peptides and the two-peptide composite significantly reduced the blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
(78 reference statements)
1
1
0
Order By: Relevance
“…As shown in Figure 3, compared with the WKY group, the contents of ACE and Ang II in the sera of the SHRs in the KB group were significantly increased (p < 0.001, p < 0.001), while the contents of ACE 2 and Ang 1-7 were significantly decreased (p < 0.05, p < 0.01), which was in agreement with the results reported by Sun et al, who found that hypertension can affect the contents of substances related to ACE regulation in the rat sera [30]. After the long-term oral administration of the fermented milk, the contents of ACE, Ang 1-7, ACE2, and Ang II in the sera of the SHRs in the Y44 group were significantly different from those in the KB group (p < 0.05, p < 0.05, p < 0.05, and p < 0.01, respectively), while the contents of ACE, Ang 1-7, ACE 2, and Ang II in the sera of the SHRs in the GY group were significantly different from those in the KB group (p < 0.01, p < 0.05, p < 0.001, and p < 0.01, respectively).…”
Section: Effect Of Fermented Milk Oral Administration On Renal Ras In...supporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure 3, compared with the WKY group, the contents of ACE and Ang II in the sera of the SHRs in the KB group were significantly increased (p < 0.001, p < 0.001), while the contents of ACE 2 and Ang 1-7 were significantly decreased (p < 0.05, p < 0.01), which was in agreement with the results reported by Sun et al, who found that hypertension can affect the contents of substances related to ACE regulation in the rat sera [30]. After the long-term oral administration of the fermented milk, the contents of ACE, Ang 1-7, ACE2, and Ang II in the sera of the SHRs in the Y44 group were significantly different from those in the KB group (p < 0.05, p < 0.05, p < 0.05, and p < 0.01, respectively), while the contents of ACE, Ang 1-7, ACE 2, and Ang II in the sera of the SHRs in the GY group were significantly different from those in the KB group (p < 0.01, p < 0.05, p < 0.001, and p < 0.01, respectively).…”
Section: Effect Of Fermented Milk Oral Administration On Renal Ras In...supporting
confidence: 91%
“…We used a previously published method to prepare the fecal sample (50 mg) from the tested animals and analyzed the SCFA levels using a gas chromatography–mass spectrometry system [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies had confirmed that SRP was a good ACE inhibitor (IC 50 = 0.046 mmol/L), in this research, the results indicated that ACE activity was inhibited in vivo leading to angiotensin decreased after administration with SRP-PLGA-MS, thus the vascular elastic fibers relaxed and the lumen of vessel expanded, thereby the blood pressure lowering ( 27 ). Other researcher found that ACE-inhibiting peptides altered the pathological morphology of the vessel wall when administered continuously for more than 1 week ( 11 , 23 ). However, in this study, due to the short duration of administration, the media thickness of the vessel wall was not pathologically altered within 48 h of a single administration.…”
Section: Resultsmentioning
confidence: 99%
“…These tissues were cut into sections–3-4 μm in size, and stained with hematoxylin and eosin. The media thickness (distance from the inner lamina to the outer lamina) and inner diameter (12 to 6, 3 to 9 o’clock positions) of the thoracic aorta were measured ( 11 , 23 ). The data were analyzed using Image-Pro Plus 6.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation